The Nyctaginaceae family (Caryophyllales) in Aguascalientes, Mexico - Sandoval Ortega, Manuel Higinio; Siqueiros Delgado, María Elena; Cerros Tlatilpa, Rosa; Ocampo, Gilberto (Instituto de Ecología, A.C., 2020)
Background and Aims: The Nyctaginaceae family is distributed in warm regions of the world, mainly in the southwest of North America and is composed by approximately 31 genera and 405 species. For Mexico, 18 genera and about 110 species are reported. The aim of the present study was to perform the taxonomic treatment and to document the Nyctaginaceae species present in the state of Aguascalientes.Methods: Collections were carried out from August 2012 to June 2015 at different sites in the state of Aguascalientes, in which the geographic coordinates and the type of vegetation were registered. The collected material was identified by means of taxonomic keys and collated with herbarium material. For taxonomic treatment, descriptions for family, genera and species, dichotomous keys for their identification and distribution maps were elaborated based on data taken in the field and from the herbarium specimens consulted.Key results: In Aguascalientes the family Nyctaginaceae is represented by six genera and 15 species, two of which are new records for the state's flora: Commicarpus scandens and Pisoniella arborescens. The genus with the highest number of species is Mirabilis with six, followed by Boerhavia with four and Allionia with two.Conclusions: Within the state, the largest number of Nyctaginaceae species is found in the Asientos and Tepezalá municipalities, in xerophilous scrub. The present study contributes to the knowledge of the flora of Aguascalientes and the family Nyctaginaceae in Mexico.